Ninth Five Year Plan (1997-2002) Electronics Industry - Planning Commission (Planning Commission, 1997)
In order to give thrust to electronics industry during the IX Plan (1997-2002), the Planning Commission set up a Working Group on electronics industry with the objectives - to review the status of electronics industry; to assess year-wise capacity and production upto 2001 -02 with an indication of the perspective upto 2005 AD; estimate the investment required; review the impact of various policy measures and suggest policy framework; examine infrastructural facilities, R&D base.
Government of India Department of Electronics
Government of India Department of Electronics